2016
DOI: 10.1002/ange.201603034
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum–Bismuth Bimetallic Chalcogenide Nanosheets for Highly Efficient Electrocatalytic Reduction of Carbon Dioxide to Methanol

Abstract: Methanol is av ery useful platform molecule and liquid fuel. Electrocatalytic reduction of CO 2 to methanol is apromising route,whichcurrently suffers from low efficiency and poor selectivity.H erein we report the first work to use aM o-Bi bimetallic chalcogenide (BMC) as an electrocatalyst for CO 2 reduction. By using the Mo-Bi BMC on carbon paper as the electrode and 1-butyl-3-methylimidazolium tetrafluoroborate in MeCN as the electrolyte,t he Faradaic efficiency of methanol could reach 71.2 %w ith ac urrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…However, using 2D nanosheets for ECR selectively to CH 3 OH has been rarely reported. Han and colleagues 81 showed that Mo-Bi bimetallic chalcogenide (BMC) nanosheets were able to reduce CO 2 to CH 3 OH with a faradic efficiency of 71.2% and a current density of 12.1 mA cm À2 , which outperform earlier reported catalysts. In contrast, CH 3 OH was not generated when bulk MoS 2 /carbon paper (CP) or Bi 2 S 3 /CP electrode was used.…”
Section: Methanol Selectivitymentioning
confidence: 91%
“…However, using 2D nanosheets for ECR selectively to CH 3 OH has been rarely reported. Han and colleagues 81 showed that Mo-Bi bimetallic chalcogenide (BMC) nanosheets were able to reduce CO 2 to CH 3 OH with a faradic efficiency of 71.2% and a current density of 12.1 mA cm À2 , which outperform earlier reported catalysts. In contrast, CH 3 OH was not generated when bulk MoS 2 /carbon paper (CP) or Bi 2 S 3 /CP electrode was used.…”
Section: Methanol Selectivitymentioning
confidence: 91%
“…The electrochemical reduction of carbon dioxide (CO 2 )into methanol (CH 3 OH) is considered as amajor target that could enable at ransition from fossil fuels to renewable fuels.T o catalyze the six-electron-six-proton reduction of CO 2 to CH 3 OH, efforts have been devoted to the use of metal oxides,m etal alloys,o rc halcogenide-based catalytic electrodes. [1][2][3][4] Most of these materials either require the use of rare metals,o ra re not selective for methanol because they cogenerate more reduced products (for example,methane or C 2 molecules). [5,6] Additionally,t he thermodynamic stability window of metal oxides is limited [7] and the reduced metal electrodes typically have low activity for CH 3 OH produc-tion, [8] leading to performance instability.O ne promising strategy to achieve high selectivity is to use molecular catalysts to precisely control the structure of the active site.…”
mentioning
confidence: 99%
“…The average total surface current density measured for Ag-Bi@GF reached 76 and 107 mA cm -2 at -1.6 and -1.8 V SCE , respectively (Fig. 9), which is very promising for a CO 2 -saturated solution at atmospheric pressure [21][22][23] although the value is lower than the critical one usually admitted for practical applications [26].…”
Section: Effect Of the Applied Potentialmentioning
confidence: 88%
“…An increase in FE has been obtained with Cu-Bi electrodes, which was attributed to a change in the local environment of Bi modulated by Cu atoms [21]. A synergistic effect has also been observed between Bi and Mo for producing methanol [23]. S-O composite involving a bimetallic Ag-Bi system has also improved Faradaic efficiency for the selective CO 2 reduction into formate.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation